Online database acceptance and doctoral dissertation quality - Mohammad Adnan; Siti Uriana Rahmawati; Maswani Maswani; Ulpah Andayani; Cinta Rahmi (Berkala Ilmu Perpustakaan dan Informasi, 2026)
Introduction: This study explores how postgraduate students at UIN Syarif Hidayatullah Jakarta use online databases to improve the quality of their doctoral dissertations.It examines perceived ease of use, perceived usefulness, and factors influencing students’ willingness to use online databases during dissertation preparation. Research Methods: The study employed a descriptive qualitative approach using semi-structured interviews, Focus Group Discussions (FGDs), and document analysis involving 30 doctoral students. Data Analysis: Data were analyzed using the interactive model of Matthew B. Miles and A. Michael Huberman, with triangulation and member checking applied to ensure validity and credibility. Results: The findings indicate that online database use enhances dissertation quality through five dimensions: expanded literature horizons, clearer identification of research gaps, stronger academic credibility, accelerated writing processes, and improved academic self-confidence. Challenges include limited access to premium databases, language barriers, interface complexity, and uneven information literacy. Conclusion: Acceptance of online databases shapes dissertation quality beyond usage intention. Perceived ease of use and usefulness translate into concrete academic outcomes, extending the Technology Acceptance Model (TAM) by linking technology acceptance with academic quality in Islamic higher education.